2021
DOI: 10.3390/nu13051637
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response of Triple-Negative Breast Cancer to Folate Restriction

Abstract: Background: Triple-negative breast cancers (TNBCs), accounting for approximately 15% of breast cancers, lack targeted therapy. A hallmark of cancer is metabolic reprogramming, with one-carbon metabolism essential to many processes altered in tumor cells, including nucleotide biosynthesis and antioxidant defenses. We reported that folate deficiency via folic acid (FA) withdrawal in several TNBC cell lines results in heterogenous effects on cell growth, metabolic reprogramming, and mitochondrial impairment. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Zhu et al (2016) demonstrated that sterol regulatory-element binding protein -1-mediated transcription of lipogenic genes and lipid production are essential for breast cancer development. However, Coleman et al (2021) reported that folate deprivation or anti-folate therapy inhibits triplenegative breast cancer cell growth by inducing mitochondrial dysfunction. The enhanced lipid transport and metabolism and folate biosynthesis caused by the gut microbiota in the BN and BM groups may participate in breast cancer occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al (2016) demonstrated that sterol regulatory-element binding protein -1-mediated transcription of lipogenic genes and lipid production are essential for breast cancer development. However, Coleman et al (2021) reported that folate deprivation or anti-folate therapy inhibits triplenegative breast cancer cell growth by inducing mitochondrial dysfunction. The enhanced lipid transport and metabolism and folate biosynthesis caused by the gut microbiota in the BN and BM groups may participate in breast cancer occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, such receptors have been proposed as a useful target in personalized therapy against BC [187,188]. This target is particularly useful in triple-negative BC (TNBC), in which reduced folate intake or the use of antifolate drugs result in mitochondrial dysfunction, which reduces metabolic plasticity [189].…”
Section: Folatesmentioning
confidence: 99%